2009
DOI: 10.1246/bcsj.82.482
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of Oxidative Aromatization Using Activated Carbon–Molecular Oxygen System in the Synthesis of 2-Arylbenzazoles: Focus on the Role of Activated Carbon

Abstract: Nineteen activated carbons, including sixteen tailor-made and three commercially available ones, were employed to investigate their role in the one-pot synthesis of 2-arylbenzazoles starting from 2-aminophenol, 1,2-diaminobenzene, or 2-aminobenzenethiol, and aldehyde via oxidative cyclization of intermediate phenolic Schiff base promoted by the activated carbon–molecular oxygen system. Tailor-made activated carbons were prepared from wood, coconut shell, and coal by the steam activation method or the chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Quinoidic groups have been pinpointed by various studies as the mediators of carbon catalysed dehydrogenations in both gas 14 and liquid phase. 36 Furthermore, they have been also identified as active sites in ODH C-C couplings of various (hetero)aryl substrates. 13,48,49 Usually, hydrogen abstraction is proposed as a reasonable mechanistic route in the gas-phase dehydrogenative reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quinoidic groups have been pinpointed by various studies as the mediators of carbon catalysed dehydrogenations in both gas 14 and liquid phase. 36 Furthermore, they have been also identified as active sites in ODH C-C couplings of various (hetero)aryl substrates. 13,48,49 Usually, hydrogen abstraction is proposed as a reasonable mechanistic route in the gas-phase dehydrogenative reactions.…”
Section: Resultsmentioning
confidence: 99%
“…32 Interestingly, Hayashi and co-workers published several convincing reports where they used untreated ACs to synthesize anthracenes, pyridines, pyrazoles and indoles under mild oxidative conditions. 11,[33][34][35][36] Furthermore, they demonstrated that untreated AC delivers higher yields of quinolines and isoquinolines than Pd/C in MeCN. 37 In this work, we show that the catalytic activity of untreated AC in oxidative dehydrogenative aromatizations can be significantly improved by an operationally easy thermal treatment, and we apply this sustainable synthetic protocol for the synthesis of the indole core structure of the progesterone receptor antagonists.…”
Section: Introductionmentioning
confidence: 99%
“…Hayashi and co-workers examined various aerobic oxidation reactions over untreated AC catalysts. 29,30 They reported that surface oxygen-containing groups, which were evolved as CO at high temperatures, were active sites for oxidative cyclization. 30 In addition, the present authors recently indicated that pyridine-type nitrogen species were active for the aerobic oxidation of xanthene.…”
Section: Resultsmentioning
confidence: 99%
“…29,30 They reported that surface oxygen-containing groups, which were evolved as CO at high temperatures, were active sites for oxidative cyclization. 30 In addition, the present authors recently indicated that pyridine-type nitrogen species were active for the aerobic oxidation of xanthene. 17 Those other surface species should catalyze the aerobic oxidation of alcohols but be less active compared with the graphite-type nitrogen species.…”
Section: Resultsmentioning
confidence: 99%
“…By virtue of the developed pore structure, large specific surface area, rich surface functional groups, high stability, and easy regeneration, AC is widely used in chemical industry, environmental protection, biology, food, and other fields as an excellent decolorization material [7]. At present, the commercially available ACs are mainly prepared by using coal, wood, and fruit shell as raw materials [8]. However, in order to meet the requirements of low-cost production in the industrial market and the current situation of forestry resources, using the petrochemical resources on the raw material with wood and coal has been limited.…”
Section: Introductionmentioning
confidence: 99%